2001
DOI: 10.1046/j.1432-1327.2001.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

A chicken hnRNP of the A/B family recognizes the single‐stranded d(CCCTAA)n telomeric repeated motif

Abstract: With the aim of identifying proteins able to interact with the C-rich single-stranded telomeric repeated motif, three nuclear polypeptides, CBNPa, CBNPb and CBNPg, with apparent mobilities in SDS/PAGE of 38, 44 and 55 kDa, respectively, were isolated from mature chicken erythrocytes by affinity chromatography. In situ UV-cross-linking experiments demonstrated that CBNPa and CBNPg interact directly with the telomeric d(CCCTAA) n repeat, whereas CBNPb does not. Moreover, they provided information on the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Raw data were analyzed by using computer software provided by the manufacturer and are reported as average masses. Assignments of the recorded mass values to individual peptides were performed on the basis of their molecular mass as previously described (21).…”
Section: Cn-ii Forms An Asp-52-phosphointermediatementioning
confidence: 99%
See 2 more Smart Citations
“…Raw data were analyzed by using computer software provided by the manufacturer and are reported as average masses. Assignments of the recorded mass values to individual peptides were performed on the basis of their molecular mass as previously described (21).…”
Section: Cn-ii Forms An Asp-52-phosphointermediatementioning
confidence: 99%
“…Gel bands were reduced, alkylated, and digested in situ with trypsin as previously reported (21). The resulting digests were separated by reverse phase-HPLC as illustrated in Fig.…”
Section: ј-Nucleotidase Inactivation By Woodward's Reagent K-tomentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] These sequences are widely dispersed in genomic DNA, [7] and proteins have been found that interact selectively with such sequences, possibly in their i-motif form; [8][9][10][11][12] this suggests that these sequences and the relevant i-motif structures might be involved in biological processes. [13] It has been reported, for example, that the i-motif upstream of the insulin gene might facilitate transcription.…”
mentioning
confidence: 99%
“…Subsequent studies showed that hnRNP A1 protect the G-rich overhang region from degradation (Dallaire, Dupuis, Fiset, & Chabot, 2000), while hnRNPs D, K and E prefer the hnRNPrich telomeric sequence (Bandiera et al, 2003;Marsich, Bandiera, Tell, Scaloni, & Manzini, 2001). hnRNP D and its isoforms not only bind to ss oligonucleotides but also disrupt G-G pairing, facilitating telomerase access (Eversole & Maizels, 2000).…”
Section: Association With Chromatin and Telomeresmentioning
confidence: 99%